2000
DOI: 10.1074/jbc.m001558200
|View full text |Cite
|
Sign up to set email alerts
|

Stomachs of Mice Lacking the Gastric H,K-ATPase α-Subunit Have Achlorhydria, Abnormal Parietal Cells, and Ciliated Metaplasia

Abstract: The H,K-ATPase of the gastric parietal cell is the most critical component of the ion transport system mediating acid secretion in the stomach. To study the requirement of this enzyme in the development, maintenance, and function of the gastric mucosa, we used gene targeting to prepare mice lacking the ␣-subunit. Homozygous mutant (Atp4a ؊/؊ ) mice appeared healthy and exhibited normal systemic electrolyte and acid-base status but were achlorhydric and hypergastrinemic. Immunocytochemical, histological, and ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
135
1
7

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(154 citation statements)
references
References 36 publications
(43 reference statements)
11
135
1
7
Order By: Relevance
“…Increased proliferation and cell turnover in this compartment were also described in patients with atrophy (Biasco et al, 1989;Miwa et al, 1997) and in animals treated with the proton pumpinhibitor omeprazole (Kakei et al, 1993(Kakei et al, , 1995. These animals, like the H,K-ATPase knockout mice in previous studies (Scarff et al, 1999;Spicer et al, 2000), showed both achlorhydria and suppressed differentiation of gastric chief cells. Therefore, it might be speculated that gastric acid represents a key factor for gastric morphogenesis.…”
Section: Dimmler Et Almentioning
confidence: 86%
“…Increased proliferation and cell turnover in this compartment were also described in patients with atrophy (Biasco et al, 1989;Miwa et al, 1997) and in animals treated with the proton pumpinhibitor omeprazole (Kakei et al, 1993(Kakei et al, , 1995. These animals, like the H,K-ATPase knockout mice in previous studies (Scarff et al, 1999;Spicer et al, 2000), showed both achlorhydria and suppressed differentiation of gastric chief cells. Therefore, it might be speculated that gastric acid represents a key factor for gastric morphogenesis.…”
Section: Dimmler Et Almentioning
confidence: 86%
“…Blood Gas and Electrolyte Analysis-Tail vein blood (50 l) was collected from adult Aqp5 ϩ/ϩ and Aqp5 Ϫ/Ϫ age-and sex-matched littermates (12-16 weeks of age, n ϭ 6 each genotype) and analyzed for gases, electrolytes, and pH as described (19).…”
Section: Hyposmotic Shock and The Associated Regulatory Volume Decreamentioning
confidence: 99%
“…, demonstrated a totally different situation from that in Kir4.1 Ϫ/Ϫ PCs: instead of secretory membranes, large vacuoles with scant microvilli and very occasional vesicular structures resembling tubulovesicles are seen in Atp4␣-deficient PCs (33). Clearly, the microvilli are long and well defined in Kir4.1 Ϫ/Ϫ secretory membranes.…”
Section: Kir41 Channels In Gastric Acid Secretionmentioning
confidence: 96%